MANAGEMENT OF ELECTION LOGISTICS 2024 PADANGSAMBIAN KLOD VILLAGE SUPPORTS THE IMPLEMENTATION OF DEMOCRATIC, FAIR AND ACCOUNTABLE ELECTIONS - Samitha, Sang Made Dwi Okayana; Putri, Putu Indah Dianti (LPPM Univ. Ibn Khaldun Bogor, 2024)
General elections are an integral part of the democratic system implemented in the Unitary State of the Republic of Indonesia, where popular sovereignty is exercised directly, publicly, freely, secretly, honestly and fairly. Elections have the main purpose as a means of selecting prospective government leaders, removing conflicts of interest, and mobilizing popular support for the State and government. To ensure the smooth running of the electoral process, one important aspect that must be managed is logistics. The logistics process in elections involves the planning, procurement, distribution, maintenance, and destruction of ballot papers. However, phenomena such as delays in logistics distribution, the addition of additional voter data, and the availability of human resources and transportation fleets can be a challenge in planning election logistics. This research explores the phenomena that occur in the planning of election logistics, focusing on Padangsambian Klod Village in West Denpasar sub-district, Bali Province. This village has good accessibility and enthusiastic community participation in the election process. However, challenges in logistics planning remain, including distribution delays, additional voter data, and the availability of human resources and transportation fleets.